1984
DOI: 10.1104/pp.75.2.372
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Conductance as a Factor Limiting Leaf Expansion of Phosphorus-Deficient Cotton Plants

Abstract: ABSITRACT Suboptimnal levels of phospborus (P) strongly inhibited leaf expansion in young cotton (Gousypium hirstum L.) plants during the daytime, but had little effect at night. The effect of P was primarily on cell expansion. Compaed to plants grown on high P, plants grown on low P had lower leaf water potentials and transpiration rates, and greater diurnal fluctuations in leaf water potential. Hydraulic conductances of excised root systems and of intact transpiring plants were determined from curves relatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
115
2
3

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(141 citation statements)
references
References 22 publications
21
115
2
3
Order By: Relevance
“…Hydraulic conductivity through detached root systems increases with increased P levels in nutrient solutions (Radin & Eidenbock, 1984) or tissue (Andersen et al, 1989). Increases in tissue P concentrations have been shown to account for a large amount of the VA mycorrhizal effect measured in Lp (Graham & Syvertsen, 1984) or whole plant water relations (Nelsen & Safir, 1982;Koide, 1985;Fitter, 1988), with some exceptions (Auge, Schekel & Wample, 1986).…”
Section: Phosphorus Nutrition and Lpmentioning
confidence: 99%
“…Hydraulic conductivity through detached root systems increases with increased P levels in nutrient solutions (Radin & Eidenbock, 1984) or tissue (Andersen et al, 1989). Increases in tissue P concentrations have been shown to account for a large amount of the VA mycorrhizal effect measured in Lp (Graham & Syvertsen, 1984) or whole plant water relations (Nelsen & Safir, 1982;Koide, 1985;Fitter, 1988), with some exceptions (Auge, Schekel & Wample, 1986).…”
Section: Phosphorus Nutrition and Lpmentioning
confidence: 99%
“…Perhaps nutrient-induced reductions in root hydraulic conductivity, which have often been reported (Radin & Boyer 1982;Radin & Eidenbock 1984;Chapin et al 1988), can generate changes in xylem tension which then act as a signal for initiating the onset of regulated cell wall changes in growing leaf tissues (cf.…”
Section: ±1 14±3mentioning
confidence: 99%
“…For example, reductions in leaf accumulation of potassium ions have been associated with reductions in cell osmotic potential which apparently caused reductions in turgor pressure, cell expansion and leaf area development (Marschner 1986). Alternatively, Radin & Boyer (1982) and Radin & Eidenbock (1984) showed that deficiencies in nitrogen or phosphorus induced reductions in root hydraulic conductivity in sunflower (Helianthus annuus L.) and cotton (Gossypium hirsutum L) plants. These reductions appeared to cause reductions in leaf turgor and leaf area.…”
Section: Introductionmentioning
confidence: 99%
“…1 B). Secondary responses to P stress include change in the hydraulic conductivity of roots, and the resulting lower water potential may be a major reason for the reduced cell expansion in leaves (Radin and Eidenbock, 1984). Other possible reasons for the P limitation-induced growth inhibition could be lower cytokinin contents or decreased cell wall elasticity (Ei-D et al, 1979; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 9 Horgan and Wareing, 1980).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%